Development of Gingerol-Loaded Nanostructured Lipid Carriers Using a Two-Step Method - Reynelda Juliani Sagala; Raditya Iswandana; Melva Louisa; Silvia Surini (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2026)
Ginger (Zingiber officinale) is well known for its beneficial effects on health, and it use as a culinary spice, mainly due to the presence of bioactive compounds such as 6-,8-, and 10-gingerol. Although 6-gingerol exhibits remarkable therapeutic potential, its clinical application is constrained by poor bioavailability and rapid metabolic degradation. Nanotechnology-based drug delivery systems have been widely explored to overcome these limitations by improving the stability, solubility, and bioavailability of bioactive compounds. Among these systems, nanostructured lipid carriers (NLCs) have attracted considerable to facilitate high drug-loading, enhanced stability, and controlled drug release. To address these issues, this study focused on formulating and characterizing gingerol using nanostructured lipid carriers. Gingerol-loaded NLCs were produced using a two-step process of high-shear homogenization followed by ultrasonication. Different total lipid contents were tested, specifically 5%, 8%, 10%, and 15%. Characterization of the resulting NLCs included particle size, polydispersity index (PDI), zeta potential, entrapment efficiency, in vitro release of gingerol, and stability over 30 days. The findings revealed that the NLC formulation with a total lipid content of 5% yielded the smallest average particle size of 208.32 ± 3.20 nm, alongside the lowest PDI of 0.231 ± 0.014, and the zeta potential measured at -25.90 ± 1.38 mV. The entrapment efficiency for this optimal total lipid was noted to be 70.65 ± 0.75%. Furthermore, stability testing conducted over a designated period demonstrated that the gingerol-loaded NLC formulation with a 5% lipid content maintained its integrity, exhibiting no significant degradation or alteration in properties. The results of this study highlight the critical role of the total lipid content in influencing the characteristics of NLC formulations achieved at 5% total lipid content, which not only improved the properties of gingerol delivery but also presented a potential approach for improving the delivery of compounds with low water solubility such as gingerol.